Late-onset peritoneal inclusion cysts (PIC) in adolescents undergoing major gastrointestinal surgery - Hadar Moran-Lev; Samuel A. Kocoshis (Elsevier, 2023)
Peritoneal inclusion cysts (PICs) are reactive, fluid-filled lesions of the peritoneal serosa that are usually present in reproductive-age women with a history of prior pelvic or abdominal surgery. In this report we presented 5 cases of females with short bowel presented with ovarian inclusion cysts during adolescence, long after abdominal surgery performed during their infancy or early childhood. Only one case was managed conservatively. Two cases had repeated episodes of pain and in two cases the cysts become infected (leading to septic shock in one) requiring long term of Intravenous antibiotic and supportive treatment. The presence of a PIC should be included in the differential diagnosis of abdominal pain in teenagers having undergone intestinal transplant or extensive intestinal resection resulting in short bowel.